On the effect of Ni additions to Fe – Cr – B high modulus steels. (5th April 2019) - Baron, C.; Springer, H.
Abstract: We studied the effect of Ni additions up to 15 wt% on microstructure and properties of cast and hot-rolled Fe – 24 Cr – 1.8 B (wt%) steels. The base alloy without Ni addition reached a stiffness/density ratio of 32.7 GPa g −1 cm 3, 400 MPa yield strength, 800 MPa ultimate tensile strength and 20% ductility. Increasing the Ni concentration resulted in a change of lattice parameters and the mean average size of the in-situ formed M2 B type boride particles. It also altered the matrix from a ferritic towards a martensitic and then austenitic constitution, which led to a decrease in the stiffness/density ratio but an increase in strength. Salt spray testing indicated that Fe – Cr – B – Ni alloys can reach a similar performance against wet corrosive attacks as conventional stainless steels. The results of this systematic study provide the basis for balancing the mechanical, chemical and physical properties, and thereby broadening the property profile of this novel alloy design concept for lightweight design. Graphical abstract: Unlabelled Image Highlights: Effects of Ni addition on microstructure and properties of Fe – Cr – B based high modulus steels. Ni alloying interacts with M2 B type particles, leading to changes in particles' size and lattice parameters. Ni alloying can be utilised to tailor physical and mechanical properties of high modulus steels. Resistance to corrosion in saltspray atmospheres appears to be comparable to conventional Fe – Cr – Ni steel.